Display density influences visual search for conjunctions of movement and orientation. - Berger, R; McLeod, P (1996)
J. Driver and P. McLeod (1992) reported that the ease of visual search for targets defined by a conjunction of movement and orientation was affected by an interaction between target movement and target-nontarget discriminability. When the orientation discrimination to distinguish target from nontarget was difficult, stationary targets were easier to find than moving targets. But when the orientation discrimination to distinguish target from nontarget was easy, moving targets were easier to find than stationary targets. H. J. Müller and J. Maxwell (1994) repeated the experiment but failed to find the interaction. The authors show that the difference between these results was due to the density of the visual displays used. With a high-density display, the authors replicate Driver and McLeod's result; with a low-density display, they replicate Müller and Maxwell's result.